Phylogenetic analysis of Arsenura Duncan (Lepidoptera, Saturniidae, Arsenurinae) based on adult morphology - de Camargo, Amabílio J. A.; Mielke, Olaf H. H.; Casagrande, Mirna M. (Zootaxa, 2011)
Arsenurinae includes 10 Neotropical genera with 74 species. Arsenura Duncan, 1841 is represented by 30 species and 13 subspecies, making it the largest genus of the subfamily. The species of this group occur both in the Andean high altitude and at sea level, but present higher biodiversity at lower altitudes. Most of the immature remain unknown; however, it is known that some larvae feed on several plant families. There are no prior studies on the phylogenetic relationship between the species of the genus. The goal of this study was to establish the relationships between Arsenura species using cladistic analysis, based on adult morphological characters. Arsenura was recovered as a monophyletic group, with the following relationships between species: ((A. meander, A. pandora)((A. polyodonta(A. orbignyana, A. xanthopus))(A. rebeli((A. mossi(A. beebei, A. ciocolatina))(A. archianassa(A. armida(A. albopicta, A. delormei)))))((A. aspasia, A. biundulata)((A. sylla,A.thomsoni)(A. cymonia(A. ponderosa(A. batesii, A. drucei))))))).